EXAMINING THE INFLUENCE OF NAP AND NAP DURATION ON ACADEMIC PERFORMANCE AMONG UNDERGRADUATE MEDICAL STUDENTS AT KMC, PESHAWAR: A GENDER-BASED ANALYSIS - Abdullah Abdullah; Muhammad Muneeb; Imdadullah Shah; Imtiaz Ullah; Haris Zaman; Khwaja Awais Ahmed; Hammad Saleem; Abdullah (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
This study examined the effects of nap and nap duration on academic performance of medical students at Khyber Medical College, Peshawar, focusing on gender differences. The study period is between March 20, 2024, and April 20, 2024. Participants completed a three-part survey. This survey helps collect students’ demographics, nap profiles, and academic profiles. The results indicate that male students who do not nap tend to perceive themselves as more proficient, while female students who nap tend to rate themselves higher. Nap duration also influences proficiency levels differently for each gender. This study found that daytime napping habits and nap lengths affect academic performance differently for male and female medical students. Non-napping males perceive higher proficiency, while napping females rate themselves higher. These findings suggest gender-specific support and intervention strategies to enhance academic success.